The auto-ethnographic turn in design - Schouwenberg, Louise 1954-; Kaethler, Michael ca. 20. Jh (Valiz, 2021)
"The Auto-Ethnographic Turn in Design' is emerging from a growing recognition of design's capacity to make sense of one's world while at the same time to express and convey this personal insight or knowledge through rich, layered, and ultimately meaningful processes or objects. Auto-ethnographic design seeks to come to terms with one's context and self' as well as the materiality that mediates these two. In doing so, it offers a vision of design that is free of commercial commissions, assumed users' needs, or well-intentioned do-goodism, and reveals a sincerity and genuine commitment in the process of design that is too often missing. The book is divided between "Ideas and Dialogues" (reflections and conversations between critics, theorists, educators, and practitioners), which ground conceptions of auto-ethnography and the "self" and explore how experiences can be relevant and meaningful starting points for design and visual art; and "Projects and Practices", which embody auto-ethnographic qualities' whereby design objects and practices are embedded with personal sentiments, experiences, desires, fears, and more" -- Provided by publisher
Keywords: Ästhetik; Design; Autoethnografie; Design / Social aspects; Design / Psychological aspects; Design / Political aspects; Design / Human factors; Conceptual art; Materialism in art; Aufsatzsammlung